Areal Energy Density: A Lithium‐Sulfur Battery with a High Areal Energy Density (Adv. Funct. Mater. 34/2014). (September 2014) - Kim, Joo‐Seong; Hwang, Tae Hoon; Kim, Byung Gon; Min, Jaeyun; Choi, Jang Wook
<x xml:space="preserve">Abstract</x> The highest areal energy density to date of a lithium‐sulfur battery is demonstrated on page 5359 by J. W. Choi and co‐workers through the combination of smart engineering of the key cell components (electrode, electrolyte, and separator). The integrated strategy suppresses both lithium polysulfide dissolution from the sulfur cathode and lithium dendrite growth from the lithium anode, leading to the highest areal capacity of 9 mAh cm−2 while preserving stable cyclability. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>